Desalination. From a questioned resource to a necessary and strategic resource during drought situations for the water supply in the Segura River Basin - Álvaro Francisco Morote Seguido (Investigaciones Geográficas)
In Spain, desalination has gained tremendous impetus in the last two decades thanks to the approval of the National Hydrological Plan (2001) and the Program A.G.U.A. (2004). This is due to two main factors: 1) The recurrent and intense droughts in recent years and, especially, the drought of the nineties in which the need to find new sources and the commitment to using unconventional water resources was highlighted (desalination and recycled reclaimed water); and 2) By changing the old hydraulic paradigm based on the increase in the water supply by means of water transfers. The aim of this research work is to analyse the role that desalination, a traditional controversial resource, has played in supplying water during the current drought 2015-2018 in the Segura River Basin (southeast of Spain) and, in particular, during the temporary closure of the Tagus-Segura Aqueduct (2017-18). In conclusion, it should be noted that desalination has become a source of vital importance that has prevented water restrictions on the coast of the south east peninsula. Consequently, the region is less vulnerable to drought and the effects of climate change.